COVID-19, law & regulation : rights, freedoms, and obligations in a pandemic - Bennett, Belinda; Freckelton, Ian R.; Wolf, Gabrielle (Oxford : Oxford University Press, 2023)
COVID-19 is the most severe pandemic the world has experienced in a century. This book analyses major legal and regulatory responses internationally to COVID-19, and the impact the pandemic has had on human rights and freedoms, governance, the obligations of states and individuals, as well the role of the World Health Organization and other international bodies during this time. The authors examine notable legal challenges to public health measures enforced during the pandemic, such as lockdown orders, curfews, and vaccine mandates. Importantly, the book contextualises the legal analysis by examining the broader social and economic dimensions of risks posed by the pandemic.
This edition also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 24, 2023).
Keywords: COVID-19 (Disease) -- Law and legislation; COVID-19 Pandemic, 2020- -- Law and legislation; Law; Laws of specific jurisdictions & specific areas of law